Evolution of antithrombotic therapy in patients undergoing percutaneous coronary intervention: a 40-year journey. (26th December 2020) - Cao, Davide; Chandiramani, Rishi; Chiarito, Mauro; Claessen, Bimmer E; Mehran, Roxana
Abstract: Since its introduction in 1977, percutaneous coronary intervention has become one of the most commonly performed therapeutic procedures worldwide. Such widespread diffusion, however, would have not been possible without a concomitant evolution of the pharmacotherapies associated with this intervention. Antithrombotic agents are fundamental throughout the management of patients undergoing coronary stent implantation, starting from the procedure itself to the long-term prevention of cardiovascular events. The last 40 years of interventional cardiology have seen remarkable improvements in both drug therapies and device technologies, which largely reflected a progressive understanding of the pathophysiological mechanisms of coronary artery disease, as well as procedure- and device-related adverse events. The purpose of this article is to provide an overview of the important milestones in antithrombotic pharmacology that have shaped clinical practice of today while also providing insights into knowledge gaps and future directions.